Dietary riboflavin deficiency induces genomic instability of esophageal squamous cells that is associated with gut microbiota dysbiosis in rats. Issue 11 (2nd November 2020) - Pan, Feng; Xu, Xin; Zhang, Ling-Li; Luo, Hong-Jun; Chen, Ye; Long, Lin; Wang, Xuan; Zhuang, Pei-Tong; Li, En-Min; Xu, Li-Yan
Abstract : Dietary riboflavin deficiency promotes carcinogen NMBA-induced esophageal tumorigenesis and is associated with gut microbiota dysbiosis in rats. Reduction of xenobiotic biodegradation and genomic instability may be the involved potential mechanisms. Abstract : Scope : Epidemiologic evidence suggests that riboflavin (RBF) deficiency is a specific nutritional predisposition for esophageal cancer. The aim of this study is to investigate the potential roles of gut microbiota in esophageal tumorigenesis caused by the RBF deficiency. Methods : Male F344 rats were subcutaneously injected with the chemical carcinogen N -nitrosomethylbenzylamine (NMBA, 0.35 mg kg −1 ). Rats were assigned to 4 groups, denoted as R6 (normal RBF, 6 mg kg −1 ), R6 N (normal RBF combined with NMBA), R6 N → R0 N (normal RBF conversion to RBF-deficiency), and R0 N → R6 N (RBF-deficiency conversion to normal RBF). Bacterial communities were analyzed based on high-throughput 16S rRNA gene sequencing. Oxidative DNA damage and double-strand break markers were studied by immunohistochemistry. Results : The R6 N → R0 N diet enhanced the incidence of esophageal intraepithelial neoplasia (EIN, 40 weeks 66.7% vs . 25 weeks 16.7%, P < 0.05). RBF deficiency and replenishment modulated the gut microbiota composition. The gut microbiota ( e.g. Caulobacteraceae, Sphingomonas and Bradyrhizobium ) affected xenobiotic biodegradation and the genomic instability of the host. Furthermore, the RBF deficiency aggravated oxidative DNA damage and DNA double-strand breaks (immunohistochemistry) in the esophageal epithelium, whereas the RBF replenishment had the opposite effect ( P < 0.05, respectively). Conclusions : RBF deficiency promotes NMBA-induced esophageal tumorigenesis, which is associated with gut microbiota-associated genomic instability, and offers new insights into the role of RBF deficiency in esophageal carcinogenesis.